Newborn bath: construction and validation of the instrument content - Maria Paula Custódio Silva; Mayline Verônica Rocha Sampaio; Nylze Helena Guillarducci Rocha; Luciana Mara Monti Fonseca; Jesislei Bonolo do Amaral Rocha; Divanice Contim (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To build and validate the content of a good practice tool in the newborn bath. Method: Methodological study, developed from December 2018 to January 2019, in a Joint Neonatal Housing Unit of a teaching hospital, in three stages: bibliographic survey, construction of the instrument and content validation by nine judges. The content validity index was used above 80% and general analysis with ten requirements. Results: The instrument was organized in three domains: before bathing, during bathing and after bathing, with a total of 20 items. Two rounds of validation were carried out to adjust the suggestions; the second presented a percentage of agreement between the judges, equal to or above 0.82. Conclusion: The instrument "Good practices in the newborn's bath" was considered representative and valid in terms of content.